MEMBANGUN WEBSITE KOMUNITAS IKATAN ALUMNI UNIVERSITAS SAHID SURAKARTA - Mohammad Arifin Nurul Qhomar; Dwi Retnoningsih; Agus Purwo Handoko (Universitas Sahid Surakarta, 2012)
Community is a group of people who share and support to each other and Collegiate is a person who has been followed of graduated from a school or university.The technological growth, development a collegiate community website can be a communication media and brotherhood between the graduated. With that technology, soit made Collegiate Relation Community Website, Sahid University of Surakarta. Collegiate Relation Community Website, Sahid University of Surakarta build uses a PHP program language and MySQL database, it is developed using data modelwith DFD, ERD, and Data Dictionary, Macromedia Dreamweaver 8 as an easier way to use the website. By website Collegiate Relation Community Website, Sahid Universityof Surakarta, graduated can interact and change information like sharing the story, vacancy, etc. Collegiate Relation Community Website is having the character ofdynamic, so the information can be served in this website always up to date. This research yield a Collegiate Relation Community Website, Sahid University of Surakarta. Assessment Quality of Collegiate Relation Community Website, SahidUniversity of Surakarta pursuant to important aspect of method McCall by random sampling using some factors which related to software operational character there arecorrectness, reliability, efficiency, integrity, portability, flexibility, usability and maintainability. Result conclusion of Collegiate Relation Community Website, SahidUniversity of Surakarta is 75,5 %, it is Good.